Transparency of Regional Health Budgets and Its Impact on Basic Immunization Coverage - Mardelina (Cattleya Darmaya Fortuna, 2025)
Background: Basic immunization coverage is strongly influenced by regional fiscal governance, particularly the quality of budget transparency that ensures adequate allocation, accurate execution, and performance accountability. Objective: To examine the effect of regional health budget transparency on basic immunization coverage in Indonesia and to explore its distribution mechanisms through allocation and implementation channels. Methods: A district/city panel study (2018–2024) using fixed effects models, difference-in-differences/event study, and mediation analysis. Transparency is operationalized as the Health Budget Transparency Index (HBTI) that combines the dimensions of depth, timeliness, and budget–performance linkages; estimation uses a one-year lag to reduce simultaneity and clustered standard errors at the district/city level. Results: A one-standard deviation increase in HBTI is associated with an increase in immunization coverage of approximately 3.20 percentage points; the effect is stable across various robustness tests. Mediation indicates the contribution of allocation channels ( 0.90 pp) and implementation ( 0.80 pp), while event studies indicate no disruptive pre-policy trends and amplifying effects 2–3 years post-adoption. Effects are greater in areas with low baselines, low fiscal capacity, and rural areas. Conclusion: Program-relevant budget transparency improves the effectiveness of immunization spending by improving allocation priorities and implementation discipline. Policy recommendations include detailed publication of sub-activities, procurement calendars, and budget–output–outcome matrices to accelerate coverage increases, with a focus on underdeveloped areas and strengthening cross-regional coordination.